Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

CD49a+CD49b+ NK cells induced by viral infection reflect an activated state of conventional NK cells - Wenhan Li; Jing Zhou; Xianwei Wang; Yuzhang Wu; Lilin Ye; Haiming Wei; Rui Sun; Zhigang Tian; Hui Peng (Science China Life Sciences, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Cloning and expression of Allophycocyanin gene from Gracilariopsis lemaneiformis and studying the binding sites of phycocyanobilin on its α and β subunits - Yalin Guo; Xiaonan Zang; Xuexue Cao; Feng Zhang; Deguang Sun; Menghui Shang; Rui Li; Zhaxi Yangzong; Xuehong Wei; Xuecheng Zhang (Journal of Applied Phycology, 2020)

Efficient removal of tylosin by nitrogen-doped mesoporous carbon nanospheres with tunable pore sizes - Xingru Hu; Junwen Qi; Rui Lu; Xiuyun Sun; Jinyou Shen; Weiqing Han; Lianjun Wang; Jiansheng Li (Environmental Science and Pollution Research, 2020)

Fluoride-Induced Alteration in the Diversity and Composition of Bacterial Microbiota in Mice Colon - Rong Fu; Ruiyan Niu; Rui Li; Baijuan Yue; Xuhua Zhang; Qiqi Cao; Jundong Wang; Zilong Sun (Biological Trace Element Research, 2020)

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Visible and near-infrared spectroscopy with chemometrics are able to predict soil physical and chemical properties - Jinbao Liu; Jiancang Xie; Jichang Han; Huanyuan Wang; Jianhong Sun; Rui Li; Shaoxuan Li (Journal of Soils and Sediments, 2020)

MiR-430 Can Affect the Mesoderm Formation and Metamorphosis of Paralichthys olivaceus by Targeting lefty Gene - Rui Li; Zhenwei Wang; Minmin Sun; Meiting Peng; Jie Qi; Zhigang Wang (Journal of Ocean University of China, 2020)

Short-term effects of particulate matter exposure on emergency room visits for cardiovascular disease in Lanzhou, China: a time series analysis - Rui Chen; Qian Gao; Jianyun Sun; Haixia Yang; Yongjun Li; Fenyan Kang; Wei Wu (Environmental Science and Pollution Research, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Systematic analysis of lncRNA expression profiles and atherosclerosis-associated lncRNA-mRNA network revealing functional lncRNAs in carotid atherosclerotic rabbit models - Yingnan Wu; Feng Zhang; Xiaoying Li; Wenying Hou; Shuang Zhang; Yanan Feng; Rui Lu; Yu Ding; Litao Sun (Functional & Integrative Genomics, 2020)

Biochar-related studies from 1999 to 2018: a bibliometrics-based review - Dongyang Li; Rui Zhao; Xing Peng; Zhifei Ma; Ying Zhao; Tiancheng Gong; Mengyang Sun; Yuxin Jiao; Tianxue Yang; Beidou Xi (Environmental Science and Pollution Research, 2020)